Comparative genomics analysis of Stenotrophomonas maltophilia strains from a community - Li, Yini; Liu, Xin; Chen, Lingzhi; Shen, Xiao; Wang, Haihong; Guo, Ruiyu; Li, Xiang; Yu, Zehui; Zhang, Xiaoli; Zhou, Yingshun; Fu, Li (Frontiers in Cellular and Infection Microbiology, 2023)
Background Stenotrophomonas maltophilia is a multidrug-resistant (MDR) opportunistic pathogen with high resistance to most clinically used antimicrobials. The dissemination of MDR S. maltophilia and difficult treatment of its infection in clinical settings are global issues. Methods To provide more genetic information on S. maltophilia and find a better treatment strategy, we isolated five S. maltophilia, SMYN41–SMYN45, from a Chinese community that were subjected to antibiotic susceptibility testing, biofilm formation assay, and whole-genome sequencing. Whole-genome sequences were compared with other thirty-seven S. maltophilia sequences. Results The five S. maltophilia strains had similar antibiotic resistance profiles and were resistant to β-lactams, aminoglycosides, and macrolides. They showed similar antimicrobial resistance (AMR) genes, including various efflux pumps, β-lactamase resistance genes (blaL1/2), aminoglycoside resistance genes [aac(6’), aph(3’/6)], and macrolide-resistant gene (MacB). Genome sequencing analysis revealed that SMYN41-SMYN45 belonged to sequence type 925 (ST925), ST926, ST926, ST31, and ST928, respectively, and three new STs were identified (ST925, ST926, and ST928). Conclusion This study provides genetic information by comparing genome sequences of several S. maltophilia isolates from a community of various origins, with the aim of optimizing empirical antibiotic medication and contributing to worldwide efforts to tackle antibiotic resistance.